Crystal structures and gas adsorption behavior of new lanthanide-benzene-1,4-dicarboxylate frameworks - Kitt Panyarat (2018)
© 2017 Six new lanthanide metal organic complexes, i.e. [La2(NO2-BDC)3(H2O)4] (1) [Ln(L)0.5(NO2-BDC) (H2O)]·3H2O (Ln = Eu (2), Tb (3), Dy (4) and Ho (5); L = BDC2−or BDC2−/NO2-BDC2-) and [Tm(NO2-BDC)1.5(H2O)]·H2O (6), have been synthesized using mixed ligands of benzene-1,4-dicarboxylic acid (H2BDC) and the in situ generated 2-nitro-benzene-1,4-dicarboxylic acid (NO2-BDC2-). Single crystal structures and topologies of the complexes are presented based on the single crystal X-ray diffraction and spectroscopic data. Whilst the structures of 1 and 6 contain negligible voids, the frameworks of 2–5 are microporous in nature and stable upon the removal of all the water molecules from the structures and thermal treatment to over 400 °C. Based on the study of 2, significant adsorption capacities for carbon dioxide (95 cm3·g−1or 4.2 mmol·g−1) and hydrogen (79 cm3·g−1or 4 mmol·g−1), as well as the remarkable stability of the framework upon the sorption/desorption experiments are revealed.